The Operational Guide - for the making markets work for the poor (M4P) approach (Second Edition) - and The Springfield Centre (SDC & DFID, 2015)
In 2008, SDC and DFID published three documents aimed at improving the understanding and use of the Making Markets Work for the Poor (M4P) approach: the M4P Synthesis, M4P Perspectives and M4P Operational Guide. Since then the field has grown, diversified and, importantly, learned much more. A second edition was commissioned to capture that learning, maintain the momentum and realise the ambition that development can still 'do better'. The second edition provides an accessible resource to help practitioners put the market systems development approach into practice. It explains the key principles and frameworks which guide effective intervention in – and development of – market systems. It addresses common challenges with examples of good practice based on practitioner experience. Who is it for? The Operational Guide is for people whose job entails trying to make market systems work better for poor women and men. These people include: Individuals currently involved in funding or implementing the approach. Development agencies wishing to incorporate market systems thinking and practice in their work. National stakeholders that wish to play a more strategic and catalytic role within market systems. What is new? Application, application, application! Whilst the key principles and frameworks will be familiar, the advice on their operational application – from start to finish – has been significantly bolstered Enhanced guidance on facilitation. Greater emphasis on what constitutes good facilitation practice, building on a wealth of practitioner experience More real-life examples. The Operational Guide is laced with examples from programmes past and present, working in a diverse array of systems Peer learning focus. Direct insights from practitioners, highlighting 'bumps in the road' and how to avoid them. The Guide aims to provide an accessible operational resource to help practitioners put the market systems development approach into practice. It explains the key principles and frameworks which guide the process of effective intervention in – and development of – market systems, addressing common challenges with examples of good practice based on practitioner experience. HOW SHOULD IT BE USED? The Guide explores, sequentially, the key elements of the implementation process: strategy, diagnosis, vision, intervention, measurement and management. It is not intended to be read from cover to cover; readers can go directly to the chapter most relevant to their needs without having read preceding chapters. However each chapter does build upon the preceding one and may refer to other chapters. THE GUIDE IS STRUCTURED AS FOLLOWS: INTRODUCTION Overview of the objectives, structure and format of the Guide CONTEXT A reminder of what market systems development means 1. STRATEGY Core principles and framework for setting programme strategy 2. DIAGNOSIS Core principles and framework for diagnosing system constraints 3. VISION Core principles and frameworks for defining and planning intervention 4. INTERVENTION Core principles and framework to guide effective intervention 5. MEASUREMENT Core principles and framework for measuring results 6. MANAGEMENT Key considerations in managing market systems development programmes GLOSSARY Definition of key terms used in market systems development